2018
DOI: 10.1104/pp.17.01648
|View full text |Cite
|
Sign up to set email alerts
|

A New Phenotyping Pipeline Reveals Three Types of Lateral Roots and a Random Branching Pattern in Two Cereals

Abstract: Recent progress in root phenotyping has focused mainly on increasing throughput for genetic studies, while identifying root developmental patterns has been comparatively underexplored. We introduce a new phenotyping pipeline for producing high-quality spatiotemporal root system development data and identifying developmental patterns within these data. The SmartRoot image-analysis system and temporal and spatial statistical models were applied to two cereals, pearl millet (Pennisetum glaucum) and maize (Zea may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Another important caveat of twodimensional (2D) growth systems is that once architectures become large and complex enough for roots to occlude one another, the ability to track the growth of individual roots is greatly diminished and usually unfeasible if grown in soil because the topology is obscured. A recent optical imaging study quantifying lateral root development in millet and maize growing in hydroponic 2D rhizotrons reported an average of 2-d-per-plant processing time using a state-of-the-art semi-automated root tracing tool (Passot et al, 2018). Hence, intense interest in X-ray and magnetic resonance-based 3D imaging for root studies has been warranted (Mooney et al, 2012;Helliwell et al, 2013;Roose et al, 2016;Morris et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another important caveat of twodimensional (2D) growth systems is that once architectures become large and complex enough for roots to occlude one another, the ability to track the growth of individual roots is greatly diminished and usually unfeasible if grown in soil because the topology is obscured. A recent optical imaging study quantifying lateral root development in millet and maize growing in hydroponic 2D rhizotrons reported an average of 2-d-per-plant processing time using a state-of-the-art semi-automated root tracing tool (Passot et al, 2018). Hence, intense interest in X-ray and magnetic resonance-based 3D imaging for root studies has been warranted (Mooney et al, 2012;Helliwell et al, 2013;Roose et al, 2016;Morris et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The growth of these roots was more or less horizontal in shallow soils and became more and more vertical with increased depth. Conversely, the growth orientation of fine roots, which most likely corresponded to the different types of laterals [13 and 26], was only marginally dependent on soil depth. This led us to develop a model for RLD estimation that considered soil depth as an important variable.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the dynamics of the increase in individual root elongation, lengths of the 10 longest laterals were assessed throughout the 11-day experiments. In previous studies, large variability in both length and elongation rate has been observed among lateral roots in maize (Cahn et al, 1989;Moreno-Ortega et al, 2017;Passot et al, 2018) and other species (Freixes, Thibaud, Tardieu, & Muller, 2002;Muller et al, 2019;Pagès, 1995). F I G U R E 1 Average length of FR697 (a) and B73 (b) primary (black and red) and seminal (blue and orange) axial roots during 11 days after transplanting (DAT) to well-watered (WW) conditions (black and blue) or a mild water deficit (MWD) treatment at a transplant Ψ w of −0.28 MPa (red and orange).…”
Section: Dynamic Responses Of Lateral Root Length Elongation Rate mentioning
confidence: 92%
“…In the MWD treatment, in contrast, the genotypes exhibited strongly divergent responses from 4 DAT. Whereas the growth pattern of B73 roots was very similar under WW and MWD conditions throughout the experiments (Figure 3b We selected the 10 longest roots, which exhibited maximum elongation rates that were similar to those of the fastest-growing category characterized previously (Moreno-Ortega et al, 2017;Passot et al, 2018). However, the growth duration exhibited in both FR697…”
Section: Dynamic Responses Of Lateral Root Length Elongation Rate mentioning
confidence: 96%